1995
DOI: 10.21273/jashs.120.5.861
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Scion and Rootstock, Topping Height, and Tree Spacing Affect Tree Size, Yield, Fruit Quality, and Economic Return

Abstract: A factorial experiment begun in 1980 included `Hamlin' and `Valencia' sweet-orange scions [Citrus sinensis (L.) Osb.], and Milam lemon (C. jambhiri Lush) and Rusk citrange [C. sinensis × Poncirus trifoliata (L.) Raf.] rootstocks, tree topping heights of 3.7 and 5.5 m, between-row spacings of 4.5 and 6.0 m, and in-row spacings of 2.5 and 4.5 m. The spacing combinations provided tree densities of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…Connor and Gómez-del-Campo (2013), who simulated radiation-limited yield response of various N-S oriented rectangular olive hedgerows, also found maximum oil yield with D/A = 1, with decrease at lower values due to shorter length of productive hedgerow per unit orchard area and slight oil yield increase at values greater than 1. There are many reports in fruit crops suggesting that light limitation in lower parts of overcrowded canopies (i.e., high D/A) reduces yield (Wheaton et al, 1995;Farina et al, 2005;He et al, 2008). In olive, Pastor et al (2007) found significant reduction of fruit number and fruit oil content in lower canopy layers of narrow olive hedgerows when D/A exceeded 1.25.…”
Section: Introductionmentioning
confidence: 94%
“…Connor and Gómez-del-Campo (2013), who simulated radiation-limited yield response of various N-S oriented rectangular olive hedgerows, also found maximum oil yield with D/A = 1, with decrease at lower values due to shorter length of productive hedgerow per unit orchard area and slight oil yield increase at values greater than 1. There are many reports in fruit crops suggesting that light limitation in lower parts of overcrowded canopies (i.e., high D/A) reduces yield (Wheaton et al, 1995;Farina et al, 2005;He et al, 2008). In olive, Pastor et al (2007) found significant reduction of fruit number and fruit oil content in lower canopy layers of narrow olive hedgerows when D/A exceeded 1.25.…”
Section: Introductionmentioning
confidence: 94%
“…The formula used for MV was based on one-half of an ellipsoid considering canopy diameters parallel and perpendicular to the row (near ground level) and maximum canopy height (Wheaton et al, 1995;Tumbo et al, 2002;Schumann and Zaman, 2005).…”
Section: Manual Tree Volume Computationmentioning
confidence: 99%
“…However, early yield advantages tend to diminish as the trees increase in size and competition for space, light, water and nutrients becomes more intensified in closely spaced groves (Savage, 1965;Carry, 1977;Tucker et al, 1991). The results of numerous studies indicated that, when practised in moderation, higher planting densities (closer spacing) and techniques to control tree size can be of considerable benefit, not only in ensuring high yields during early life of trees but also in increasing the efficiency of harvesting and spraying operations (Childers, 1978;Wheaton et al, 1995). Therefore, proper control of tree size is essential to the success of closely spaced groves (Tucker and Philip, 1967).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer application practices in citrus production in Florida are based on tree age and projected yield (Obreza et al 2008a) and these properties can be related directly to tree size. The manual measurement of citrus tree canopy volume (Wheaton et al 1995) for individual trees is laborious and time consuming. A rapid alternative method, is ultrasound-based measurement of tree canopy volume .…”
Section: Introductionmentioning
confidence: 99%